A feasibility randomised control trial of acceptance and commitment therapy for spinal cord stimulation surgery patients - Akiens, Samantha (2016)
Introduction: This thesis explored the feasibility of conducting a randomised control trial (RCT) of Acceptance and Commitment Therapy (ACT) within patient’s Spinal Cord Stimulation (SCS) treatment pathway. Previous ACT literature has reported that this is an effective intervention with persons with chronic pain, even when in a self-help format. Whilst this growing body of ACT literature is promising, chronic pain is a broad term used for a number and varying levels of disability. Chronic neuropathic pain (CNP) is usually more complex and resistant to treatment. According to NICE guidelines SCS should be the last treatment option for CNP sufferers. However, there is currently a dearth of literature exploring the effectiveness of the addition of a psychological interventions with the SCS population. Objectives: The aim of this thesis was to explore the parameters of interest in ACT with SCS patient population including recruitment, acceptability of intervention and treatment signals.